Pengaruh Fitur Mobile Banking Terhadap Minat Penggunaan Pada Nasabah - Amri, Sahrial; Kristijadi, Emanuel (ITB AAS Indonesia Surakarta, 2025)
Abstract This study aims to analyze the influence of perceived usefulness, ease of use, perceived security, feature availability, and service quality on the intention to use mobile banking among customers at PT. BPR Penataran Kabupaten Blitar. The research is motivated by the Financial Services Authority new policy on the implementation of BPR and BPRS products, which encourages them to develop banking digitalization programs to meet customer needs and enhance competitiveness in the digital era. Data was collected from 320 respondents, who were Civil Servants with Work Agreements (ASN P3K), using a questionnaire. The analysis was conducted using a multiple linear regression model with the help of SPSS 21.00 software. The results indicate that the regression model used is feasible. Individually, all five independent variables—perceived usefulness, ease of use, perceived security, feature availability, and service quality have a positive and significant effect on the intention to use mobile banking. The outcome of this study can serve as a guide for PT. BPR Penataran Kabupaten Blitar to optimize its mobile banking services and become a reference for other financial institutions in increasing the adoption and utilization of their digital services. Keywords: mobile banking, intention to use, perceived usefulness, ease of use, perceived security, feature availability, service quality